Digitalization of national economy - L. P. Goncharenko; S. A. Sybachin (Вестник университета, 2019)
Digitalization of the national economy is one of the key state tasks. The gradual transition to a digital model of development will increase the competitiveness of Russian products on international markets and it will also contribute to the improvement of national security. Analysis of the implementation of information and communication technologies in the national economy shows significant lag behind the leaders. The positive economic effect of modern digital technologies integration in business model of transport enterprises has been considered on the example of the automotive industry.